Salivary gland ultrasound in the diagnostic workup of juvenile Sjögren's syndrome and mixed connective tissue disease - Manuela Krumrey-Langkammerer; Johannes-Peter Haas (BMC, 2020)
Abstract Background Juvenile Sjögren's Syndrome (jSS) is a rare phenomenon that may appear as primary jSS or associated with mixed connective tissue disease (MCTD) and other autoimmune diseases as secondary jSS. With currently no standard diagnostic procedures available, jSS in MCTD seems to be underdiagnosed. We intended to describe and identify similar distinct salivary gland ultrasound (SGUS) findings in a cohort of primary and secondary jSS patients, focusing on sicca like symptoms and glandular pain/swelling in the patients'history. Methods We present a single-center study with chart data collection. B-mode examinations of salivary glands were obtained with a linear high-frequency transducer and evaluated using the scoring-system of Hocevar. Inclusion criteria were: (i) primary or secondary jSS and/or (ii) diagnosis of MCTD and additionally (iii) any presence of sicca like symptoms or glandular pain/swelling. Results Twenty five patients with primary (pjSS) and secondary jSS (sjSS) were included in the study (n = 25, 21 female, 4 male), with a median age of 15.3 years at the time of first visit and a mean disease duration of 4.9 years. Pathologic SGUS findings were observed in 24 of 25 patients, with inhomogeneous parenchymal appearances with hypoechoic lesions present in 96% of patients. At least one submandibular gland was affected in 88.5% of the whole group, and all patients in the MCTD-group. Twenty of twenty five patients were scanned and scored on a second visit. Pre-malignancies or mucosa-associated lymphoid tissue (MALT) were detected in biopsies of three patients (Hocevar scoring of 40, 33, and 28). Conclusion SGUS in patients with pjSS and sjSS is a helpful first-line tool to detect and score salivary gland involvement, in particular when keratoconjunctivitis sicca, xerostomia, or glandular swelling occurs. Juvenile MCTD patients have a significant risk of developing secondary jSS. We propose SGUS as a method in the diagnostic workup and screening for inflammatory changes. Further studies have to determine the predictive value of SGUS for follow up.